Further Insight into Uranium and Thorium Metaphosphate Chemistry and the Effect of Nd3+ Incorporation into Uranium(IV) Metaphosphate. Issue 9 (18th February 2015) - Yu, Na; Klepov, Vladislav V.; Neumeier, Stefan; Depmeier, Wulf; Bosbach, Dirk; Suleimanov, Evgeny V.; Alekseev, Evgeny V.
Abstract: A tetragonal modification of uranium polymetaphosphate U(PO3 )4, a mixed U 4+ /Nd 3+ polymetaphosphate "(U0.62 Nd0.38 )(PO3 )4 ", and two new tetraphosphates, Th(P4 O12 ) and U(P4 O12 ), were synthesized. The structures of the obtained materials were characterized by X‐ray diffraction and Raman spectroscopy. The presence of Nd in (U0.62 Nd0.38 )(PO3 )4 was proven by energy‐dispersive X‐ray spectroscopy (EDX), and the measured degree of substitution for U agrees well with the X‐ray crystallography results; however, the mechanism of the necessary charge compensation could not be identified. The cation arrangements in the crystal structures of thorium and uranium polymetaphosphates have been studied in terms of Voronoi–Dirichlet polyhedra. Different conformations of the tetraphosphate polyanions were observed in the crystal structures of Th(P4 O12 ) and U(P4 O12 ). The Raman spectrum of a single crystal of Th(P4 O12 ) was recorded, and the bands were assigned. Abstract : Two new polymorphic modifications of uranium metaphosphate are obtained, and their crystal structures are elucidated as well as those of previously reported thorium and uranium tetraphosphates. The uranium atoms are partially substituted by neodymium atoms in the structure of one of the uranium metaphosphates, and the substitution significantly affects the structure.